РОЗРАХУНОК ЕЛЕКТРОТЕПЛОВИХ ПРОЦЕСІВ В ІНДУКЦІЙНІЙ КАНАЛЬНІЙ ПЕЧІ В УСТАЛЕНОМУ РЕЖИМІ НА ОСНОВІ ТЕОРІЇ ТЕПЛОВИХ КІЛ - Щерба, А.А.; Подольцев, О.Д.; Перетятко, Ю.В.; Золотарьов, В.М.; Білянін, Р.В. (Інститут електродинаміки Національної академії наук України, 2021)
Based on the theory of thermal circuits, a computer model of an induction channel furnace has been developed, which is used to obtain industrial copper wire rods in the mode of continuous casting. The model allows calculating the established electrothermal processes considering the flows of cold and molten metal in its core. In the developed thermal model, it is proposed to consider the convection fluxes of heat in the metal using controlled current sources. The temperature distribution in the active zone of the channel furnace is calculated, and the influence of the mass flow of metal at the inlet and outlet of the furnace on the non-uniformity of temperature distribution in the active zone is shown. The obtained results allow determining the required electric power of the furnace at different values ​​of the flow rate of the metal that moves continuously through its core while heating to a given temperature. The developed model is relatively easy to implement, using the Matlab/Simulink package, and allows online to estimate the melt temperature in different zones depending on the electric power consumed by the furnace and the metal consumption at the outlet of the furnace, as well as to determine rational modes of its operation. Ref. 7, fig. 4.